Growth of Halal Tourism in Pamekasan: Is It Influenced by Majelis Ulama? - Aang Kunaifi; Taufik Hidayat; Fadali Rahman (Research Synergy Foundation, 2021)
Purpose- This paper aims to determine the effectiveness of the Islamic tourism guidelines set by the Indonesian Ulama Council in Pamekasan on the development of halal tourism in that regency. In particular, this paper analyzes the suitability of the principles, objectives and characteristics of halal tourism that already exist in Pamekasan. Design/methodology/approach- This paper is written based on a very credible and representative source, which was explored in depth interview with several halal tourism owners, local community leaders, daily administrators of the ulama council, and regional regulators. The refinement of the analysis is carried out comprehensively by connecting the results of observations to the halal tourism guidelines that have been released by MUI Pamekasan Regency. Findings- The results show that the adaptation of sharia to the phenomenon of halal tourism growth in Pamekasan does not refer to the textual guidelines that have been made, but rather the personal figure of the Ulama Council which represents the institution. Social implication- The results show that the socialization of the principles, objectives and characteristics of halal tourism must involve local figures, such as the kyai who owns the pesantren. The existence of these figures has actually become a legitimacy for the community to perceive a halal tourist destination that is suitable for consumption by the community. Originality/value- This paper reveals a novelty in the specification aspect of tourism development objects in Pamekasan, with the intention of finding the character of halal tourism that is acceptable to the public.